THE PHASE COMPOSITION OF BIOCERAMIC PROTECTIVE LAYERS OF HEALTHY AND PATHOLOGICAL HATCHING HEN’S EGGS: THE PHASE COMPOSITION OF BIOCERAMIC PROTECTIVE LAYERS OF HEALTHY AND PATHOLOGICAL HATCHING HEN’S EGGS - Bordunova, Olga; Lupinova, Olena; Denysov , Roman (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this article we show results of structural characteristics of bioceramic protective eggshell layer of hatching eggs, which consists of calcium carbonate in different crystalline forms. We have experimentally proved that negative factors of environment, genetic factors and mistakes connected to birds holding technology lead to changes at phase composition of eggshell calcium carbonate that, in turn, can influence the essential characteristics of developing embryos.